Asynchronous stochastic dynamics and the spatial prisioner's dilemma game - Grilo, Carlos Fernando Almeida (2009)
We argue that intermediate levels of asynchronism should be explored when one uses evolutionary games to model biological and sociological systems. Usually, only perfect synchronism and continuous asynchronism are used, assuming that it is enough to test the model under these two opposite update methods. We believe that biological and social systems lie somewhere between these two extremes and that we should inquire how the models used in these situations behave when the update method allows more than one element to be active at the same time but not necessarily all of them. Here, we use an update method called Asynchronous Stochastic Dynamics which allows us to explore intermediate levels of asynchronism and we apply it to the Spatial Prisoner’s Dilemma game. We report some results concerning the way the system changes its behaviour as the synchrony rate of the update method varies.